Monolithic CMOS instrumentation amplifiers for ECG signals - Almazan, Sherwin Paul Roldan (2007)
Instrumentation amplifiers (in-amps) are important signal conditioning blocks in many electronic systems requiring precise measurements, particularly in biomedical monitoring devices. Because of the in-amp's high common-mode rejection ratio (CMRR), high input impedance, and low offset voltage, it is suitable for handling critical low-voltage biomedical signals, even in the presence of relatively high-energy noise. The goal of this project is to implement eight different monolithic in-amp circuits. In-amps are classified either as voltage-mode or current-mode. For voltage-mode in amps, four main configurations were investigated, namely: (1) subtractor, or single op-amp; (2) subtractor with input buffers; (3) 3-op-amp, which is the most commonly used in-amp topology; and (4) 2-op-amp, which is simply a cascade of two inverting amplifiers. Meanwhile, current-mode in-amps are generally implemented using positive second generation current conveyors (CCII+), which are composed of an op-amp and current mirror blocks. Four main current-mode configurations were chosen, namely: (1) conventional 2-current conveyor; and (2) 2-current conveyor with an op-amp at the output; (3) 3-current conveyor; and (4) improved 2-current conveyor. Simulations on the voltage-mode topologies achieved a CMRR of around 90dB for a DC gain of 200, and a power consumption of less than 2.5mW using a single power supply of 2.5V. The current-mode in-amps, on the other hand, yielded a CMRR of greater than 165dB for a gain of 100. The chosen op-amp topology, which is used as the building block for all the in-amp configurations, is adapted from a previous research on CMOS rail-to-rail op-amps in the Intel Microprocessors Laboratory and Microelectronics and Microprocessors Laboratory, and is designed for in-amp application. On the other hand, the current conveyor, which has not yet been studied and researched on in the laboratory, is characterized and designed specifically for current-mode in-amp operation. All the in-amp topologies are designed for handling biomedical signals, specifically that of the Electrocardiogram (ECG), and are implemented using 0.25um CMOS process.